2020
DOI: 10.3390/en13061418
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Groundwater Flow on the Thermal Performance of a Novel Borehole Heat Exchanger for Ground Source Heat Pump Systems: Small Scale Experiments and Numerical Simulation

Abstract: New small-scale experiments are carried out to study the effect of groundwater flow on the thermal performance of water ground heat exchangers for ground source heat pump systems. Four heat exchanger configurations are investigated; single U-tube with circular cross-section (SUC), single U-tube with an oval cross-section (SUO), single U-tube with circular cross-section and single spacer with circular cross-section (SUC + SSC) and single U-tube with an oval cross-section and single spacer with circular cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 37 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Indicatively, the effect of groundwater flow on the thermal performance of a BHE for GSHP systems was studied in the form of small-scale experiments and numerical simulations [135]. The authors concluded that it was advantageous to use a U-tube BHE with an oval cross-section in regions of potentially fast groundwater flow.…”
Section: The Effect Of Groundwater Flowmentioning
confidence: 99%
“…Indicatively, the effect of groundwater flow on the thermal performance of a BHE for GSHP systems was studied in the form of small-scale experiments and numerical simulations [135]. The authors concluded that it was advantageous to use a U-tube BHE with an oval cross-section in regions of potentially fast groundwater flow.…”
Section: The Effect Of Groundwater Flowmentioning
confidence: 99%
“…Ma et al investigated the effect of groundwater migration on the BHE, heat exchange between ground heat exchangers and changes in the surrounding soil from heat conduction to the coupled mode of conduction and convection [59]. The presence of groundwater advection can significantly increase heat transfer and accelerate the possibility of soil restoration, as studied by Serageldin et al [60]. Lei et al investigated whether groundwater flow and the interaction of underground pipe groups will affect heat transfer efficiency and ground temperature field distribution, thus affecting the design and operation of ground source heat pumps [58].…”
Section: Introductionmentioning
confidence: 99%
“…Bae et al [64] evaluated the thermal performance of different types of BHE pipes using the Thermal Response Test (TRT) under the same field and test conditions and found that the average thermal resistance of the well could be an important factor in TRT, but the effect of the increased thermal conductivity of the pipe material itself was not significant. Another important point is that the presence of groundwater advection can greatly increase heat transfer and speed up the possibility of ground restoration, as studied by Serageldin et al [65], Lei et al [2], Park et al [66], and Sakata et al [67].…”
Section: Introductionmentioning
confidence: 99%